Останні результати точних вимірювань на експерименті NA62 - Boboc, P.-C.; on behalf of the NA62 collaboration (Publishing house "Academperiodika", 2024)
Experiment NA62 at CERN collected the world’s largest dataset of charged Kaons, the main goal being the measurement of the B (K+ → π+vv- ). New results from the analyses of rare kaon and pion decays using data samples collected in 2017–2018 are presented. A sample of K+ → π+γγ decays was collected using a minimum-bias trigger and measurement of the branching ratio, study of the di-photon mass spectrum, and the first search for production and prompt decay of an axion-like particle with gluon coupling in the process K+ → π+A, A → γγ are reported. Additionally, a sample of π0 → e+e- decays was collected, using a dedicated scaled down di-electron trigger, and preliminary results for the branching ratio are reported.